Designing and Developing of Learning Class Grouping Applications Base on Genetic Algorithms - Denny Kurniadi (Universitas Negeri Padang, 2023)
The student learning class grouping application is a crucial service within the academic lecture system to facilitate learning and make it easier for educators to choose strategies and teaching methods to optimize academic achievement. In this grouping application, a genetic algorithm is implemented to optimize the distribution of learning classes, adopting the concept of biological evolution where the initial population of learning groups is considered as